As we have always done: Indigenous freedom through radical resistance - Simpson, Leanne Betasamosake (Indigenous Americas, 2017)
Across North America, Indigenous acts of resistance have in recent years opposed the removal of federal protections for forests and waterways in Indigenous lands, halted the expansion of tar sands extraction and the pipeline construction at Standing Rock, and demanded justice for murdered and missing Indigenous women. In As We Have Always Done, Leanne Betasamosake Simpson locates Indigenous political resurgence as a practice rooted in uniquely Indigenous theorizing, writing, organizing, and thinking. Indigenous resistance is a radical rejection of contemporary colonialism focused around the refusal of the dispossession of both Indigenous bodies and land. Simpson makes clear that its goal can no longer be cultural resurgence as a mechanism for inclusion in a multicultural mosaic. Instead, she calls for unapologetic, place-based Indigenous alternatives to the destructive logics of the settler colonial state, including heteropatriarchy, white supremacy, and capitalist exploitation.
Keywords: amérique du nord; amériques; approches et analyses; autochtones; colonialisme; com5170; cours; discours dominant; fem1300; histoire et politique; militance; pol4212; premier cycle; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne Betasamosake; Régimbald, Anne-Marie (Collection Proses de combat, 2018)
"On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale."-- Renaud-Bray.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; militance; ojibwa; premier cycle; premières nations; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires